Association between dietary intake of carotenoids and metabolic dysfunction-associated fatty liver disease in US adults: National Health and Nutrition Examination Survey 2017-March 2020 - Jiahui Yu; Peisen Guo (Cambridge University Press, 2024)
Abstract Objective: To assess the relationship between dietary intake of α-carotene, β-carotene, β-cryptoxanthin, lycopene and lutein+zeaxanthin (LZ) and occurrence of metabolic dysfunction-associated fatty liver disease (MAFLD). Design: Cross-sectional study design. The MAFLD diagnosis was based on hepatic steatosis and metabolic dysregulation. Carotenoid intake was adjusted for using an energy-adjusted model. Logistic regression and restricted cubic spline (RCS) analyses were used to assess the relationships, with sensitivity analysis to validate the findings. Weighted quantile sum regression (WQS) was used to explore the combined effect of these carotenoids on MAFLD. Subgroup analyses were conducted to identify population-specific associations. Setting: National Health and Nutrition Examination Survey (NHANES) 2017-March 2020. Participants: This study included 5098 individuals aged 18 years and older. Results: After adjusting for potential confounders, a weak inverse association was observed between α-carotene and β-carotene intakes and MAFLD occurrence (all P value <0·05). The highest quartile of β-carotene intake showed a significantly lower occurrence of MAFLD compared with the lowest quartile (OR = 0·65; 95 % CI: 0·44, 0·97). RCS analysis showed that a significantly lower occurrence of MAFLD was associated with a higher intake of the four carotenoids, excluding lycopene. Furthermore, the WQS analysis revealed a negative relationship between combined carotenoid intake and MAFLD occurrence (OR = 0·95, 95 % CI: 0·90, 1·00, P = 0·037). Subgroup analyses showed dietary carotenoid intake was associated with reduced MAFLD occurrence in populations aged 50-69 years, females, physically active individuals and non-drinkers. Conclusion: Higher dietary intake of carotenoids is associated with lower MAFLD occurrence. However, this relationship varies among individuals of different ages, sexes and lifestyles.